"Distributional aspects of Ireland's fiscal adjustment": a comment - O'Hagan, John (Economic & Social Studies, 1992)
There is little, if anything, I can add to the fine paper by Tim Callan and Brian Nolan in the way of statistical data or direct comment. Their treatment of the topic has been comprehensive, impartial and professional. The main message to emerge from their paper, for me, was that the fiscal retrenchment and economic growth of the period did not have any particularly adverse distributional consequences ? at a macroeconomic level at least. This is in marked contrast to the experience of the UK in the first half of the 1980s, where the income share of the bottom 50 per cent fell quite considerably over the period. The main reason for this is that fiscal adjustment in Ireland was accompanied by growth in incomes and employment, thereby avoiding many of the adverse distributional consequences experienced in the UK.
Keywords: Fiscal policy; Ireland; Income distribution; Inequality